Can damselfly larvae serve as bioindicator species for assessing contamination of organophosphate esters in aquatic environments? - Wanru Zhang; Mei Wang; Ang Zhao; Yangyang Liu; Yuting Ren; Huijie Dang; Jianzhong Xu; Chao Wei; Yuxia Yang; Haoyu Liu (Ecological Indicators)
Damselfly larvae have been widely used to evaluate the environmental quality of freshwater ecosystems. However, there have been limited studies on the pollution characteristics of organophosphate esters (OPEs) in damselfly larvae. This study investigated the pollution profiles, influencing factors, and biological enrichment of OPEs in a total of 358 damselfly larvae for the first time. The results demonstrated that the concentration of OPEs in the damselfly larvae ranged from 20.56 to 2363.02 ng/g wet weight (ww), exceeding levels reported in previous studies on other aquatic organisms. Tris(2-butoxyethyl) phosphate (TBEP) was identified as the main OPE, ranging from 1.56 to 2318.94 ng/g (ww) and accounting for 7.59–98.13 % of total OPEs detected. Damselfly larvae exhibited significant biological enrichment for TBEP with an enrichment factor of 249,917 L/kg, probably due to their inherent high sensitivity to this pollutant. However, there was no significant correlation between logKow (octanol-water partition coefficient) and log BCF (bioconcentration factor), suggesting that logKow may not be the sole factor affecting biological enrichment of OPE compounds in damselfly larvae. OPE concentrations in damselfly larvae showed a positive correlation with water temperature, whereas a significantly negative correlation with total nitrogen levels. The main sources contributing to OPE pollution were daily activities and ship traffic, industrial production processes, and pesticide applications in agricultural practices. These findings suggest that damselfly larvae can serve as bioindicators for assessing OPE compound contamination in aquatic environments.